Regulation of sleep disorders in patients with traumatic brain injury by intestinal flora based on the background of brain-gut axis - Zhanfeng, Niu; Liang, Wu; Jing, Kang; Jinbo, Bai; Yanjun, Chen; Hechun, Xia (Frontiers in Neuroscience, 2022)
Objective This study investigates whether people with sleep disorders following traumatic brain injury exhibit altered intestinal flora. The changes may allow us to gain a better understanding of the role of intestinal flora in patients with sleep disorders after traumatic brain injury, which may give us insights into curing the sleep disorder after traumatic brain injury (TBI). Method We analyzed the intestinal microbial colony structure in the feces of the 28 patients in the normal sleep group and the sleep disorder group by 16SrDNAsequencing technology. The bioinformatics method was used to analyze the intestinal flora change in the v3-v4 region of patients with biorhythm disorder and to observe the difference between the two groups. Results Group grouping comparison and analysis of the evolutionary cladistic map showed the intestinal flora of patients with normal sleep after TBI was mainly Bacilli and Lactobacillales, while that of patients with sleep disorders was mainly Lachnospiraceae and Bacteroidales. The histogram of group value distribution by grouping comparison and analysis showed that Lachnospiraceae, Bacteroidales, Bacteroidia, and Bacteroidetes were dominant in the sleep disorder group. A relative abundance map of species with significant differences by group grouping comparison showed the main manifestations of intestinal flora are Firmicutes, Bacilli, Lactobacillales, Streptococcaceae, and Bacteroidetes. The normal sleep group was dominated by Bacilli, Lactobacillales, Streptococcus, and Veillonella, while in the sleep disorder group, Lachnospiraceae, Bacteroidales, Bacteroidia, and Bacteroidetes were the main species. It was found that there were also significant differences in intestinal flora abundance between the two groups after TBI. After statistics processing, it was compared with the normal sleep group, Lactobacillus, Streptococcus, Oribacterium and Rothia, Actinomyces, Streptophyta, TM7-3 bacteria, and Serratia, showing a significant reduction in the sleep disorder group (P < 0.05). However, Odoribacter, Lachnospiraceae, and Bilophila increased significantly (P < 0.05). Conclusion The sleep disorders of patients after TBI can be closely related to intestinal flora disturbance, and its internal mechanism needs further study. Intestinal flora has the potential to be a new therapeutic target.